Paliativní onkologická péce v systému poskytování zdravotní péce v Královéhradeckém kraji: vlastní zkusenosti - Slovácek, L; Priester, P; Kopecký, J; Slovácková, B; Svecová, D; Petera, J; Filip, S (Klinicka onkologie, 2011)
Palliative cancer care is an active treatment and nursing intervention in patients in whom cancer therapy has been withdrawn due to untreatable progression of the cancer disease. The main aim of palliative cancer care is to ensure the best possible quality of life of a cancer patient and the patient's family members. Palliative cancer care is provided in two basic forms, general and specialized. In the present paper, the authors discuss palliative cancer care and its implementation into clinical practice with reference to their own experience in providing this care.
Keywords: paliativní péče; Terminal Care; nádory; Humans; péče o umírající; lidé; Neoplasms; Palliative Care; kvalita života; Quality of Life